eBay as a viable solution for e-entrepreneur : the case of GemsMystery. - Ng, Rong Chang. (2008)
The dissertation argues eBay as a viable tool for e-entrepreneurs. To examine its suitability, a business venture selling gem stones is set up and its process is documented. Recommendations are provided at the end to intending entrepreneurs and current eBay sellers.